2002
DOI: 10.1046/j.1365-2486.2002.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon balance and radiative forcing of Finnish peatlands 1900–2100 – the impact of forestry drainage

Abstract: Natural peatlands accumulate carbon (C) and nitrogen (N). They affect the global climate by binding carbon dioxide (CO2) and releasing methane (CH4) to the atmosphere; in contrast fluxes of nitrous oxide (N2O) in natural peatlands are insignificant. Changes in drainage associated with forestry alter these greenhouse gas (GHG) fluxes and thus the radiative forcing (RF) of peatlands. In this paper, changes in peat and tree stand C stores, GHG fluxes and the consequent RF of Finnish undisturbed and forestry‐drain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(145 citation statements)
references
References 44 publications
(68 reference statements)
11
131
1
2
Order By: Relevance
“…However, rates of peat accumulation also are dependent on carbon inputs to soils. Others also have found that long-term drainage can stimulate above-and below-ground tree productivity, and soil carbon sequestration as silvic peat [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, rates of peat accumulation also are dependent on carbon inputs to soils. Others also have found that long-term drainage can stimulate above-and below-ground tree productivity, and soil carbon sequestration as silvic peat [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…28). In some boreal regions, then, the sustained drying or drainage of peatlands in the absence of wildfire could have a negative feedback to climate change, at least in the short term, although reduced carbon uptake by trees as stands mature could diminish this effect 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Management of organic soils may alter carbon cycling. The main threat for carbon storage is drainage, causing increased CO 2 emissions (Minkkinen et al, 2002;Hooijer et al, 2009). Drainage helps to remove the excess water and, consequently, the upper soil layer is enriched with oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…The changes of biomass, growth, and mortality of trees could reflect a distribution of responses Months Months to resource availability and site condition dynamics (Feeley et al, 2007) and diversity shifting (Astiani, 2016). Our previous study demonstrated that reduced rainfall in peatlands lowered the water table (R= -0.44) from the peat surface (Astiani, 2014) which has been demonstrated to have positive effects on Net Primary Production in some northern peatlands (Laiho & Laine, 1997;Minkkinen, Korhonen, Savolainen, & Laine, 2002;Laiho, Vasander, Penttilä, & Laine, 2003). Even though lowering of the water table level due to the establishment of drainage ditches reduced the biomass growth of the trees, when we calculated cumulatively within the six years of assessments (before and post canal presence) it showed that a significant additional growth occurred, whereby stand basal area of trees increased by 27%.…”
Section: Effects Of Canal/drainage Ditches On Forest Dynamicsmentioning
confidence: 98%